Evaluation of sire on multiple traits through factor analysis - Jaiswal, U C; Khanna, As; Sangwan, M L (The Indian Journal of Animal Sciences, 2011)
In the present paper a new method of ranking sires on multiple traits has been proposed and illustrated with live data. The data on 4 economically important traits, age at first calving (days), peak yield (kg), first lactation yield (lg) and first calving interval (days) of 219 daughters belonging to 11 sires of Hariana breed of cattle were collected tor the present investigation. Correlation matrix of4 traits was subjected to principal component analysis for the extraction of factors. The results revealed that 73.33% of the variance among all the variables is accounted for by 2 common factors. First factor having high loadings on peak yield and first lactation yield was labeled as production factor. Second factor having high loadings on first calving interval and age at first calving was designated asreproduction factor. Regression coeflicients of factors on variables, estimated by using multivariate multiple regression analysis and average performance of the daughters of each sire for difTerent traits/variables were used in obtaining scores on each sire in respect of the production factor.